The relationship between specific problematic internet use and hope: academic exhaustion as mediator and mattering as moderator among Chinese university students - Xiu-Mei Chen; Yu-fu Ning; Gordon L. Flett; Xiao-Ling Liao; Jeffrey Hugh Gamble; Lingling Li; Xing-Yong Jiang; I-Hua Chen; Mark Griffiths; Pei-Jin Lin; Chung-Ying Lin (BMC Psychology)
Abstract Problematic social media use (PSMU) and problematic gaming (PG) among university students as specific types of problematic internet use (PIU) have become a growing concern. PSMU and PG may lead to negative outcomes such as academic exhaustion and diminished hope. However, previous studies have not simultaneously considered the associations among these variables from the perspective of Stressor-Strain-Outcome model. Furthermore, the concept of 'mattering'—the feeling of being valued and important to others and 'fear of not mattering' in this dynamic is notably under-investigated. The present study aimed to examine the associations among these variables and evaluated whether mattering profiles moderated the associations involving PIU among university students. A survey was conducted among 3,035 university students in China, with an average age of 19.24 years (SD = 1.83). The sample included 52% males and 48% females from 19 different universities. The Bergen Social Media Addiction Scale, the Internet Gaming Disorder Scale-Short Form, the General Mattering Scale, the Fear of Not Mattering Inventory, the Maslach Burnout Inventory–Student Survey, and the Dispositional Hope Scale were utilized to evaluate PSMU, PG, general mattering, fear of not mattering, academic exhaustion, and hope, respectively. Furthermore, latent profile analysis was used to categorize students into distinct mattering profiles based on measures of general mattering and fear of not mattering to others. Correlational analyses indicated that PSMU and PG were associated with greater academic exhaustion, reduced hope, and higher levels of fear of not mattering. Mediation analysis identified academic exhaustion as a mediator in the relationships between PSMU and hope, as well as between PG and hope. Profile analyses identified a group of students distinguished by exceptionally low levels of general mattering. Mattering profiles acted as moderators of the associations between PG and academic exhaustion, and between academic exhaustion and hope. PG negatively affected students' hope through academic exhaustion, while different mattering profiles had diverse associations. Customized intervention strategies focused on boosting hope and feelings of mattering, and reducing fears of not mattering are needed to reduce vulnerability to PG and PSMU.